Predictive factors for severe COVID-19 infection in Terengganu state of Malaysia - Awang, Hafizuddin; Ahmad, Mohd Hanief; Mohamed, Kamarul Azhar; Wahab, Azmani; Rashid, Norafidah Abdul; Arwit, Hasnan; Abd Rahman, Mohd Anuar; Embong, Kasemani (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: COVID-19 has a varied clinical presentation and may progress to severe form which could be fatal. Determination of risk factors for severe infection would be beneficial in averting COVID-19 mortality in Terengganu setting. Materials and Methods: A casecontrol study between mild and severe COVID-19 groups was conducted in Terengganu state from 1st March 2020 until 31st January 2021 based on retrospective record review. Individuals with laboratory RT-PCR confirmed positive test for COVID-19 were included as study samples. Descriptive statistics, simple and multiple logistic regression analyses were employed for statistical analysis. Results: There were 2142 COVID-19 cases in Terengganu during the studied period. The proportion of severe COVID-19 infection was 2.1% (95%CI: 0.01, 0.03). Among the severe COVID-19 cases, their mean (±SD) age was 52 (±16) and majority of them were male (59.1%) and had comorbidity (56.8%). The common symptoms among severe COVID-19 cases included fever (68.2%), cough (63.6%), coryza (22.7%), sore throat (13.6%) and anosmia (11.4%). Multiple logistic regression revealed older age, presence of comorbidity, having symptoms of fever, cough and anosmia as the significant associated factors for severe COVID-19 with adjusted odds ratio (AOR) of 1.07 (95%CI: 1.03, 1.11), p<0.001; AOR 5.97 (95%CI: 2.09, 17.01), p=0.001; AOR 4.78 (95%CI: 1.63, 14.05), p=0.004; AOR 4.81 (95%CI: 1.70, 13.60), p=0.003; and AOR 8.39 (95%CI: 1.39, 50.33), p=0.020,respectively. Conclusion: Knowing the predictive factors for severe COVID-19 would facilitate clinicians in timely identification of high-risk cases for delivering prompt treatment and intervention. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 269-274